Resolving the Human Remains Crisis in British Archaeology - Mike Pearson; Tim Schadla-Hall; Gabe Moshenska (Papers from the Institute of Archaeology, 2011)
Human remains are a fundamental part of the archaeological record, offering unique insights into the lives of individuals and populations in the past. Like many archaeological materials human remains require distinctive and specialised methods of recovery, analysis and interpretation, while technological innovations and the accumulation of expertise have enabled archaeologists to extract ever greater amounts of information from assemblages of skeletal material. Alongside analyses of new finds, these advances have consistently thrown new light on existing collections of human remains in museums, universities and other institutions. Given the powerful emotional, social and religious meanings attached to the dead body, it is perhaps unsurprising that human remains pose a distinctive set of ethical questions for archaeologists.
Keywords: reburial; Church of England; druids; religion; burials; human remains